Depletion-All-Around Operation of the SOI Four-Gate Transistor - Akarvardar, Kerem; Cristoloveanu, Sorin; Gentil, Pierre; Schrimpf, Ronald D.; Blalock, Benjamin J. (IEEE transactions on electron devices, 2007)
In the silicon-on-insulator four-gate transistors (\hbox{G}^{4}\hbox{-}\hbox{FETs}) , the conducting channel can be surrounded by depletion regions induced by independent vertical metal-oxide-semiconductor gates and lateral JFET gates. This unique conduction mechanism named depletion-all-around (DAA) enables majority carriers to flow in the volume of the silicon film far from the silicon/oxide interfaces. Especially when the interfaces are driven to inversion, the control of the lateral JFET gates on the conduction is maximized, while the sensitivity of the volume channel to the oxide and interface defects is minimized. This leads to excellent analog performance, low noise, and reduced sensitivity to ionizing radiation. The \hbox{G}^{4}\hbox{-}\hbox{FET} properties in DAA mode are presented from multiple perspectives: experimental results, 3-D device simulations, and analytical modeling.